ANALISIS KUALITAS PELAYANAN PENGUJIAN KENDARAAN BERMOTOR DI KABUPATEN TEGAL (DI LIHAT DARI IKM) - Lailatul Istiqomah Dewi; Nina Widowati; Aloysius Rengga (Journal of Public Policy and Management Review, 2013)
The test vehicle is a vehicle assigned to address safety issues in the field of publictransport safety concerns for users at both the regional and national level. This study aims toidentify and menganilisis quality of services performed by the Department of Transportation,Communication and Information Tegal regency. Type used is descriptive qualitative, by usingreference measurements on basis of the satisfaction indext KEP MENPAN No.63/7/2003which consists of 14 elements "relevan", "valid" and "reliable". The result of the satisfactionindex calculation for obtaning a yield of 74,08 or in the good category (B). To improve thequality of care testing of motor vehicles so much better, employee testing vehicles in Tegalregency should pay attention to the service user satisfaction by adding facilities andinfrastructure, as well as providing strict sanctions or penalties for employees who absentduring working hours or working days..